Factors Influencing MSME’s Interest In Transacting In E-Commerce - Fabillah, Ikhsan Habib; Prasetyo, Tri Joko; Sudrajat, Sudrajat (Basecamp Economics PubMed, 2024)
The purpose of this study is to provide empirical evidence regarding the factors that influence MSME interest in transacting in e-commerce. This research was conducted in Lampung province which consists of 13 districts and 2 municipalities with analysis of MSME that have used e-commerce as a place to sell, where the sample in this study was 400 respondents. The sampling technique used was nonprobability sampling. The data analysis method used is a quantitative method using the Structural Equation Model (SEM) model. The results of this research show that perceived usefulness, perceived ease to use, social perception do not influence MSMEs’ interest in transacting in e-commerce. Meanwhile, perceived trust, perceived enjoyment and perceived profits have a positive and significant effect on MSME interest in transacting in e-commerce